What About the Workers? / Workers and the Transition to Capitalism in Russia - Burawoy Michael; Clarke Simon; Fairbrother Peter; Krotov Pavel (Verso, 1993)
This book questions whether Russia is in transition to capitalism and looks behind the political and ideological debates to focus on the development of the social relations of production, and on the class struggles to which these give rise. Introduction: Class Struggle and the Development of Capitalism in Russia, The Contradictions of ''State Socialism'', The Crisis of the Soviet System, The Soviet Transition from Socialism to Capitalism: Worker Control and Economic Bargaining in the Wood Industry, Trade Unions and the Working Class, The Origins of the Independent Workers' Movement and the 1989 Miners' Strike, Beyond the Mines: The Politics of the New Workers' Movement, The Strikes of 1991 and the Collapse of the Soviet System, After the Coup: The Workers' Movement in the Transition to a Market Economy, Privatization and the Development of Capitalism in Russia, Bibliography.